Методика и результаты учета численности молоди речной камбалы (Platichthys flesus) и тюрбо (Scophthalmus maximus) в восточной Балтике в 1986 и 1987 г. - Vitinsh, M.Ya. (1989)
A total of 106 exploratory catches taken in June and September 1986 and 1987 at 5 fishing stations throughout the Latvian coast were aimed at further perfection of recruitment predictions for the flounder commercial stock. Altogether 3773 0-group, 1- and 2-year-old flounders and 128 turbot fingerlings have been examined. A method of the survey has been described. It has been found that the June surveys of 1-year-old fish are the most reliable. In September one may get the first preliminary estimate of the 0-group abundance. The main young fish concentration areas have been noted. The 1985 year-class of flounder was estimated to be average, the 1986 - abundant, and the 1987 year-class of poor abundance. The low water temperatures of 1987 caused the low growth rate of young fish and, perhaps, poor survival of larvae. The share of 1-year-old and 0-group turbot in the beach seine catches constituted 3 and up to 20 % of the same group flounder number respectively. С целью совершенствования прогнозирования пополнения промыслового запаса речной камбалы в июне и сентябре 1986 и 1987 г.г. на пяти станциях вдоль латвийского побережья проведено 106 ловов мальковым береговым неводом. Исследованы 3773 сеголетка, годовика и двухгодовика речной камбалы и 128 мальков тюрбо. Описана методика их учета. Установлено, что наиболее достоверные результаты дает учет годовиков в июне. В сентябре можно получить первую ориентировочную оценку численности поколения в возрасте сеголетка. Выявлены основные районы концентрации молоди. Поколение речной камбалы 1985 года рождения оценено как среднее, 1986 года - как урожайное, 1987 года - как неурожайное. В 1987 году в связи с низкой температурой воды отмечен низкий темп роста молоди, и, по-видимому, низкая выживаемость личинок. Доля тюрбо в уловах береговым неводом составила: годовиков - около 3 %, сеголетков - до 20 % от количества речной камбалы соответствующего возраста. 13. ausgabe des sonderheftes über fischereiliche untersuchungen der DDR und der UDSSR in der Ostsee. 13. выпуск ...